Microwave-Induced Synthesis of Chitosan Schiff Bases and Their Application as Novel and Green Corrosion Inhibitors: Experimental and Theoretical Approach - Haque J.; Srivastava V.; Chauhan D.S.; Lgaz H.; Quraishi M.A. (My University, 2025)
Environmentally friendly three chitosan Schiff bases (CSBs) were first time synthesized under microwave irradiation by the reaction of chitosan and aldehydes [benzaldehyde (CSB-1), 4-(dimethylamino)benzaldehyde (CSB-2), and 4-hydroxy-3-methoxybenzaldehyde (CSB-3)] and characterized by IR and NMR spectroscopy. The corrosion inhibition performance of the synthesized inhibitors was studied by the electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP). The results show that all the Schiff bases (CSBs) act as effective corrosion inhibitors for mild steel in 1 M HCl solution. Among the synthesized Schiff bases, CSB-3 exhibited the maximum inhibition efficiency of 90.65% at a very low concentration of 50 ppm. The EIS results showed that the CSBs inhibit corrosion by the adsorption mechanism. The PDP results show that all the three Schiff bases are mixed-type inhibitors. The formation of inhibitor films on the mild steel surface was supported by scanning electron microscopy/energy dispersive X-ray analysis and Fourier-transform infrared spectroscopy methods. The adsorption of CSBs on the mild steel surface obeys the Langmuir adsorption isotherm. The theoretical studies via density functional theory and molecular dynamics simulation corroborated the experimental results. © Copyright © 2018 American Chemical Society.